The Impact Of English Language On The Existence Of Indonesian Language In The Age Of Globalization - Revi Septiani Lutfi (Pusat Riset dan Inovasi Nasional, 2023)
Globalization is not only disseminating information and technology to develop the human life, but it also brings cultures with new languages which are then absorbed and utilized by people. Likewise, English has turned into an international language which is able to be mastered by various Indonesian people. However, the use of English in Indonesia is increasingly symptomatic and fades the Indonesian language. The phenomenon is unallowed since its dominance can damage the development of Indonesian language which makes its construction necessary. Thus, this research is expected to raise public awareness to uphold the Indonesian language amidst globalization.